Adjuvant Therapy in Early-Stage Endometrial Cancer: A Systematic Review of the Evidence, Guidelines, and Clinical Practice in the U.S. (12th May 2014) - Latif, Nawar A.; Haggerty, Ashley; Jean, Stephanie; Lin, Lilie; Ko, Emily
Abstract: Endometrial cancer is the most common gynecologic malignancy in the U.S., with an increasing incidence likely secondary to the obesity epidemic. Surgery is usually the primary treatment for early stage endometrial cancer, followed by adjuvant therapy in selected cases. This includes radiation therapy [RT] with or without chemotherapy, based on stratification of patients into categories dependent on their future recurrence risk. Several prospective trials (PORTEC-1, GOG#99, and PORTEC-2) have shown that the use of adjuvant RT in the intermediate risk (IR) and the high-intermediate risk (HIR) groups decreases locoregional recurrence (LRR) but has no effect on overall survival. The ad hoc analyses from these studies have shown that an even larger LRR risk reduction was seen within the HIR group compared with the IR group. Vaginal brachytherapy is as good as external beam radiotherapy in controlling vaginal relapse where the majority of recurrence occur, and with less toxicity. In the high-risk group, multimodality therapy (chemotherapy and RT) may play a significant role. Although adjuvant RT has been evaluated in many cost-effectiveness studies, high-quality data in this area are still lacking. The uptake of the above prospective trial results in the U.S. has not been promising. Factors that are driving current practices and defining quality-of-care measures for patients with early-stage disease are what future studies need to address. Abstract : Several prospective trials have shown that use of adjuvant radiation therapy (RT) in the intermediate risk and the high-intermediate risk groups decreases locoregional recurrence but has no effect on overall survival. Although the costs and benefits of adjuvant RT have been evaluated in many cost-effectiveness studies, high-quality data are lacking. Future studies need to address the factors driving current practices and defining quality-of-care measures for patients with early-stage disease.